2019
DOI: 10.1200/po.18.00324
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating Tumor DNA Profiling of Advanced Biliary Tract Cancers

Abstract: PURPOSE Recent advances in molecular diagnostic technologies have allowed for the evaluation of solid tumor malignancies via noninvasive blood sampling, including circulating tumor DNA (ctDNA) profiling. We sought to characterize the ctDNA genomic alteration landscape in patients with biliary tract cancers (BTCs). PATIENTS AND METHODS From January 2015 to February 2018, 124 patients with BTC at the Mayo Clinic Comprehensive Cancer Center underwent ctDNA testing using a clinically available assay. The majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 24 publications
6
59
1
Order By: Relevance
“…Tumor-based (whether tissue and/or liquid where tissue is not available) genetic testing using NGS platforms should become standard of care for all metastatic CCA patients [7]. This should be endorsed by guidelines and societies so that payers would reimburse as opposed to patients/physicians being responsible for fighting denials when ordered resulting in added financial costs/anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-based (whether tissue and/or liquid where tissue is not available) genetic testing using NGS platforms should become standard of care for all metastatic CCA patients [7]. This should be endorsed by guidelines and societies so that payers would reimburse as opposed to patients/physicians being responsible for fighting denials when ordered resulting in added financial costs/anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10]24 To our knowledge, the detailed comprehensive genomic landscape of biliary tract cancers by using clinicalgrade ctDNA as well as its concordance analysis with tissue-DNA are limited. 25 We now demonstrate that each biliary tract cancer patient has distinct pattern of ctDNA and tissue-DNA genomic alterations which are frequently druggable and that targeted matched therapies based on the molecular profiling are associated with higher response rates and longer progression-free survival.…”
Section: Discussionmentioning
confidence: 83%
“…A previous study reported that 55% of patients with biliary tract cancers had therapeutically relevant characterized ctDNA alterations although genes considered as targetable were somewhat different with our study. 25 Altogether, nearly all biliary tract cancer patients had unique pattern of genomic alterations in ctDNA and tissue-DNA NGS, indicating that these two different sequencing techniques can be complementary. These findings also suggest the potential for precision clinical trials in biliary tract cancers, as well as that customized molecular targeting based on each individual genomic portfolio may be necessary to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study that evaluated the utility of ctDNA analysis in patients with advanced BTC enrolled 124 patients (70% patients with iCCA) who underwent ctDNA-based molecular profiling utilizing a clinically available NGS-based assay (Guardant 360) [39]. In this study, at least one therapeutically relevant alteration was observed in 55% of patients, and 21% of patients had one of the frequently occurring alterations, which included BRAF mutations, ERBB2 amplification, FGFR2 fusions, FGFR2 mutations, and IDH1 mutations.…”
Section: Circulating Tumor Dna (Ctdna)-based Molecular Profilingmentioning
confidence: 99%